Weight-adjusted tinzaparin for venous thromboembolism prophylaxis in bariatric surgery patients weighing 160 kg or more. Issue 198 (February 2021) - Li, A.; Eshaghpour, A.; Tseng, E.K.; Douketis, J.D.; Anvari, M.; Tiboni, M.; Siegal, D.M.; Ikesaka, R.T.; Crowther, M.A.
Abstract: Introduction: Bariatric surgery patients experience an increased risk of venous thromboembolism (VTE), however, the optimal dose of low-molecular-weight heparin for VTE prophylaxis remains uncertain. Currently, St. Joseph's Healthcare Hamilton utilizes a weight-adjusted tinzaparin dosage (50 to 75 units/kg rounded to nearest pre-filled syringe) for postoperative VTE prophylaxis. Objectives: This study analyzed the safety of weight-adjusted tinzaparin for VTE prophylaxis in bariatric surgery patients weighing ≥160 kg. Methods: This was a retrospective study involving patients weighing ≥160 kg that underwent bariatric surgery from September 2015 to September 2019. Patients received a single dose of weight-adjusted subcutaneous unfractionated heparin (UFH) [5000 or 7500 IU] immediately prior to surgery, subcutaneous UFH [5000 IU, 7500 IU, or unspecified] immediately postoperatively, and either 10, 000 or 14, 000 IU of tinzaparin, beginning on the day after surgery, for 10 days. Intra-operative sequential compression devices could be used at the attending surgeon's discretion. Occurrence of VTE and major bleeding within 30 days of surgery were assessed. Results: A total of 389 patients were included for analysis, all patients received in-hospital follow-up while 349 patients had also 30-day follow-up. For the primary safety and efficacy analysis of in-hospital events, VTE and major bleeding rates were 0.26% [95% CI 0.01%–1.44%] (1/389) and 0.77% [95% CI 0.21%–2.24%] (3/389) respectively. For patients with 30-day follow-up VTE and major bleeding rates were 0.57% [95% CI 0.1%–2.07%] (2/349) and 1.43% [95% CI 0.61%–3.3%] (5/349) respectively. Conclusions: Weight-adjusted tinzaparin was associated with a low risk of bleeding and VTE events, supporting its use for VTE prophylaxis for patients weighing ≥160 kg. Highlights: Bariatric surgery patients are at an increased risk to venous thromboembolism (VTE). Weight-adjusted heparin regimes for VTE prophylaxis remain heterogenous. We analyzed a weight-adjusted tinzaparin regime in patients weighing 160 kg or more. VTE rates were 0.57% while bleeding rates were 1.43%. Weight-adjusted tinzaparin was associated with a low risk of bleeding and VTE events.